Social justice and library work a guide to theory and practice - Bales, Stephen (Chandos Publishing, an imprint of Elsevier, 2018)
Although they may not have always been explicitly stated, library work has always had normative goals. Until recently, such goals have largely been abstract; they are things like knowledge creation, education, forwarding science, preserving history, supporting democracy, and safeguarding civilization. The modern spirit of social and cultural critique, however, has focused our attention on theconcrete, materialrelationships that determine human potentiality and opportunity, and library workers are increasingly seeing the institution of the library, as well as library work, as embedded in a web of relations that extends beyond the library’s traditional sphere of influence. In light of this critical consciousness, more and more library and information science professionals are coming to see themselves as change agents and front-line advocates of social justice issues. This book will serve as a guide for those library workers and related information professionals that disregard traditional ideas of "library neutrality" and static, idealized conceptions of Western culture. The book will work as an entry point for those just forming a consciousness oriented towards social justice work and will be also be of value to more experienced "transformative library workers" as an up-to-date supplement to their praxis.--Provided by publisher.